Robust multi-variable control of continuous yeast drying. (June 2022) - Seidel, Carsten; Dürr, Robert; Bück, Andreas
Abstract: This work considers robust moisture content and activity control in a continuous convective drying for particulate bio-materials. The major process uncertainty is in the kinetics of the second (falling-rate) drying period. Robust feedback controllers in the multi-variable and de-central case are designed to guarantee desired product specifications. The advantages of the robust controllers are discussed in comparison with a conventional PI controller. The case study presented is the drying of baker's yeast in a fluidized bed dryer. The results show constant performances concerning the uncertainty of the drying kinetics and disturbance rejection at different operating points. Highlights: Robust multivariable controller design for convective drying. Constant controller performance concerning various process uncertainties and operating points. Baker's yeast in fluidized bed dryer as case study.